Solifluction resulting from one-sided and two-sided freezing: Field data from Svalbard - Matsuoka, Norikazu; Hirakawa, Kazuomi (National Institute of Polar Research, 2000)
P(論文) Two years of observation of soil movement on three Arctic slopes underlain by permafrost demonstrate convex downslope profiles at two depths, corresponding respectively to the middle and basal parts of the active layer The absence of superficial movement reflects the paucity of diurnal freeze-thaw action throughout the year and soil desiccation in summer The middle layer movement is attributed to annual frost creep/gelifluction associated mainly with frost heave during downward freezing and subsequent thaw subsidence This type of movement prevails where the lower part of the active layer is composed of coarse materials that reject ice lensing, and over the long term eventually develops typical solifluction sheets or lobes In contrast, the basal layer movement represents plug-like flow originating from thawing of ice lenses developed during upward freezing from the top of permafrost Plug-like flow occurs where the whole active layer consists of muddy sediments Such a deep movement is rarely accompanied by a specific surface feature, despite causing large mass transport departmental bulletin paper